Evidence of anuran diversity in the La Colonia Formation (Upper Cretaceous), Chubut, Patagonia, Argentina - Muzzopappa, Paula (2014)
The La Colonia Formation (Campanian-Maastrichtian), a sedimentary succession that represents a continental to marginal marine depositional environment, crops out along the southeastern margin of the Somuncurá Plateau in Chubut Province, Argentina. Several vertebrate groups (including fishes, anurans, turtles, plesiosaurs, snakes, dinosaurs, and mammals) have been reported in the fossil assemblages recovered from the middle part of this succession. Fieldwork during the last 15 years has provided new fossil localities and a great amount of vertebrate remains. Among the latter, some bones have been undoubtedly identified as belonging to anurans although their poor preservation precludes their accurate taxonomic assignment. The same applies to most of the rest of Late Cretaceous anuran fossil remains from Patagonia which, although abundant, are broken and disarticulated. The fragmentary nature of these remains obscures the taxonomic composition of the anuran fauna by the end of the Cretaceous in Patagonia, other than documenting the presence of pipids and neobatrachians. New remains collected in a thin bonebed at Norte de Cerro Bayo 2 Locality, along with previously recovered material from El Uruguayo Locality, reveal the presence of a variety of frogs. The evidence consists of three premaxillae (MPEF-PV 10890-8, MPEF-PV 10891-10) which, although incomplete, show such a significant morphological diversity so as to point to the presence of three different neobatrachian species. Further study of these remains might contribute substantially to our knowledge of the Patagonian batrachofauna in the Cretaceous, a key interval for anuran evolution considering the high speciation rate estimated by recent molecular analyses.